Improving Storability of “Nanfeng” Mandarins by Treating with Postharvest Hot Water Dipping - İbrahim Kahramanoğlu; Chuying Chen; Yao Chen; Jinyin Chen; Zengyu Gan; Chunpeng Wan (Journal of Food Quality)
The current research aimed at studying the possibility of improving the postharvest storability of “Nanfeng” mandarins by hot water dipping (HWD) treatment. The research was conducted in two phases. Firstly, two different temperatures (50 and 55°C) were tested for three different dipping durations (2, 3, and 4 min) on the mandarin fruits, and the best combination was defined for the prevention of weight loss and fruit decay. Next, the optimal treatment (HWD at 50°C for 3 min) was used in further studies to test the effects on the postharvest fruit quality attributes. Regular measurements were performed to determine total soluble solid (TSS) content, titratable acid (TA) content, vitamin C (VC) content, total sugar content, respiration rate, malondialdehyde (MDA) content, and activities of superoxide dismutase (SOD) enzyme, polyphenoloxidase (PPO) enzyme, and peroxidase (POD) enzyme. According to the results obtained, HWD treatment was found to prevent the loss of TSS, TA, and VC contents during the storage period. The HWD-treated fruits were also found to have a lower respiration rate and MDA content as compared with control treatment. Furthermore, HWD treatment significantly enhanced the activities of SOD, POD, and PPO which are known to enhance tolerance to lipid peroxidation and are associated with the fruit protection from injuries and pathogens. Present results also suggest that the activation of the SOD and POD enzymes is highly related to the respiratory activities of the fresh produce. This suggests that the HWD can be used to improve the storability of “Nanfeng” mandarins by maintaining the postharvest physical and biochemical quality.